2004
DOI: 10.1029/2004jd004583
|View full text |Cite
|
Sign up to set email alerts
|

Increasing river discharge in the Eurasian Arctic: Consideration of dams, permafrost thaw, and fires as potential agents of change

Abstract: Discharge from Eurasian rivers to the Arctic Ocean has increased significantly in recent decades, but the reason for this trend remains unclear. Increased net atmospheric moisture transport from lower to higher latitudes in a warming climate has been identified as one potential mechanism. However, uncertainty associated with estimates of precipitation in the Arctic makes it difficult to confirm whether or not this mechanism is responsible for the change in discharge. Three alternative mechanisms are dam constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
249
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(263 citation statements)
references
References 45 publications
9
249
1
4
Order By: Relevance
“…This points to the importance of establishing the source of the growing river component in the Arctic Ocean freshwater budget. Increasing precipitation has been suggested as the main driver of increasing river runoff (Dyurgerov and Carter 2004;McClelland et al 2004). However, contradictory trends in discharge and precipitation have also been reported (Berezovskaya et al 2004;Milliman et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This points to the importance of establishing the source of the growing river component in the Arctic Ocean freshwater budget. Increasing precipitation has been suggested as the main driver of increasing river runoff (Dyurgerov and Carter 2004;McClelland et al 2004). However, contradictory trends in discharge and precipitation have also been reported (Berezovskaya et al 2004;Milliman et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Serreze et al (2002) however found only low correlation between P-E and runoff across the pan-Arctic drainage basin, except for the Lena basin. Several studies have discussed a possible contribution of melting permafrost to increased runoff (Serreze et al 2002;Adam and Lettenmaier 2008;Dyurgerov et al 2010), but at least for the Eurasian Arctic, the total volumes of melting permafrost that are needed to explain the long-term runoff increases seem unrealistic (McClelland et al 2004). …”
Section: Discussionmentioning
confidence: 99%
“…The causes for these changes are unclear but the spring discharge increase has been attributed to an earlier snowmelt associated with warmer spring conditions, and changes in winter streamflow are perhaps associated with an increase in the depth of the active layer (seasonally frozen and thaw zone above the permafrost) under a warming climate (Yang et al 2002). McClelland et al (2004) suggested that increased precipitation was a key factor in streamflow augmentation, but not permafrost thaw or forest fire. Déry & Wood (2005) noted a flow reduction from northern continental Canada, including the Hudson Bay drainage.…”
Section: Natural Flowsmentioning
confidence: 99%
“…low runoff in drought years, floods during intense rainfall, and the warmed climate due to global warming effects [Intergovernmental Panel on Climate Change, 2001;Jiang and Shi, 2003;Romanovicz, 2007]. However, most researchers have focused on the flooding processes, occurrence mechanics and flood frequency in the river basin, along with regulation by dams and irrigation [McClelland et al, 2004;Berezovskaya et al, 2004;Onuchin et al, 2006]. Only a few studies have been conducted so far on the subject of riverine responses to the extreme drought events in drought years [Chen et al, 2001], especially to combined extreme drought event and underway impounding of the Three Gorges Dam (TGD).…”
Section: Introductionmentioning
confidence: 99%